PENGGUNAAN BUAH MENGKUDU(MorindacitrifoliaL.)UNTUK MENURUNKAN TEKANAN DARAH TINGGI - Sari, Cici Yuliana (Majority, 2015)
Abstract Along with the adventure of time sand technology, thus causing some changes in people lifestyle such as changes inthe term socio-economic, environment, also changes in population structure and change on patterns of disease infectious disease, that had been know long as the most frequent disease in the world, now has been replace by non-infection disease. One of non-infection disease which very dangerous is hypertension. Hypertension is also called the silent killer because hypertension often kill a patient insidiously, it could kill without showing any sign or symptoms. In Indonesia, the use of herbs for treating various diseases has been done for a long time, because of the availability of variety of plants that can be used to reduce the risk and side effects of consuming syntetic drugs. Noni (MorindacitrifoliaL.)was able to reduce blood pressure. Scopoletin, an active substance contained in noni, has know the potential of reducing peripheral resistance. Another active substance contained in noni was xeronin, which act as diuretic that can increase the volume of urine. Noni (MorindacitrifoliaL.) is safe to use because it is classified in the non-toxic substances. Keywords:hypertension, noni, scopoletin, xeronin Abstrak Seiring dengan perkembangan zaman dan teknologi, mendorong perubahan pola gaya hidup masyarakat seperti perubahan sosial ekonomi, lingkungan, perubahan struktur penduduk serta perubahan pola penyakit dari penyakit infeksi menjadi penyakit tidak menular (PTM).Salah satu penyakit tidak menular yang sangat berbahaya adalah hipertensi.Hipertensi juga disebut silent killer karena penyakit ini sering tidak menimbulkan gejala namun dapat meningkatkan morbiditas dan mortalitas.Di Indonesia sejak dahulu telahmemanfaatkan bahan herbal untuk pengobatan berbagai penyakit, karena tersedianya berbagai tanaman yang dapat dimanfaatkan dan mengurangi risiko efek samping karena penggunaan obat sintetis.Mengkudu (Morindacitrifolia L.)dapat menurunkan tekanan darah karena kandungan bahan aktif diantaranya adalahscopoletin dapat menurunkan resistensi periferdan xeroninbekerja sebagai diuretik yang dapat meningkatkan volume urin.Mengkudu(Morindacitrifolia L.) aman dikonsumsi karena digolongkan dalam zat yang tidak toksik. Kata kunci:hipertensi, mengkudu, scopoletin, xeronin